Impact of self-reported lifetime depression or anxiety on effectiveness of mass distribution of nicotine patches. Issue 5 (19th August 2016) - Kushnir, Vladyslav; Sproule, Beth A; Zawertailo, Laurie; Selby, Peter; Tyndale, Rachel F; Leatherdale, Scott T; Cunningham, John A
Abstract : Background: Large-scale public health initiatives providing free nicotine replacement therapy have been shown to increase smoking cessation rates; however, their effectiveness among the highly prevalent population of smokers with depression and anxiety disorders has not been explored. The aim of this study was to investigate the influence of lifetime history of depression or anxiety on smoking cessation success following the free distribution of nicotine patches. Method: In the context of a randomised controlled trial, a secondary analysis was conducted on 1000 adult regular smokers randomised to be mailed a 5-week supply of nicotine patches or to a no intervention control group. Participants were divided into subgroups based on the presence of self-reported lifetime diagnosis of depression and anxiety. Results: Irrespective of self-reported lifetime history of depression or anxiety, odds of self-reported cessation at 6 months were significantly greater among groups receiving nicotine patches compared to no intervention control (no history of depression or anxiety: OR 2.20; 95% CI 1.05 to 4.63; history of depression or anxiety present: OR 3.90; 95% CI 1.28 to 11.88). Among nicotine patch recipients only, quit outcomes did not differ between those with and without self-reported lifetime depression or anxiety in models unadjusted and adjusted for differences in demographic and smoking characteristics. Conclusions: The mass distribution of free nicotine patches (without behavioural support) is effective among smokers with or without lifetime history of depression or anxiety alike, providing further support for the adoption of similar initiatives as a means of promoting tobacco cessation on a population level. Trial registration number: NCT01429129, Post-results.